Palmitate Stimulates the Epithelial Sodium Channel by Elevating Intracellular Calcium, Reactive Oxygen Species, and Phosphoinositide 3-Kinase Activity. (2nd December 2018) - Wang, Qiu-Shi; Liang, Chen; Niu, Na; Yang, Xu; Chen, Xiao; Song, Bin-Lin; Yu, Chang-Jiang; Wu, Ming-Ming; Zhang, Zhi-Ren; Ma, He-Ping
Abstract : Previous studies indicate that the epithelial sodium channel (ENaC) in the kidney is upregulated in diabetes mellitus. Here, we show that ENaC single-channel activity in distal nephron cells was significantly increased by palmitate, a free fatty acid which is elevated in diabetes mellitus. We also show that palmitate increased intracellular Ca 2+ and that after chelating intracellular Ca 2+ with BAPTA-AM, palmitate failed to affect ENaC activity. Treatment of the cells with 2-aminoethoxydiphenyl borate (2-APB, an inhibitor of IP3 receptors) abolished the elevation of both intracellular Ca 2+ and ENaC activity. Treatment of the cells with apocynin (an NADPH oxidase inhibitor), dithiothreitol/NaHS (reducing agents), or LY294002 (a phosphoinositide 3-kinase (PI3K) inhibitor) prevented palmitate-induced ENaC activity, whereas thimerosal (an oxidizing agent) mimicked the effects of palmitate on ENaC activity. However, these treatments did not alter the levels of intracellular Ca 2+, indicating that elevation of reactive oxygen species (ROS) and activation of PI3K are downstream of the signaling cascade. Since we have shown that ROS stimulate ENaC by activating PI3K, these data together suggest that palmitate first elevates intracellular Ca 2+, then activates an NADPH oxidase to elevate intracellular ROS and PI3K activity, and finally increases ENaC activity via the activated PI3K.